SIKAP DAN PRESTASI BELAJAR PKn SISWA KELUARGA LENGKAP DAN KELUARGA SINGLE PARENT - Herida Herida; Sudjarwo Sudjarwo; Adelina Hasyim (Jurnal Studi Sosial / Journal of Social Studies, 2013)
This study applies a quantitative research design. The sampling technique used in this research is purposive sampling. To measure the differences between the attitude and the achievement tests results simultaneously, this study used Anatest program. The results show: scores of students’ attitude between complete families and single parent families achieve a scale of 0.4900.05, thus Ho is accepted; achievement between students complete families and  single parent families achieve a score of 0.6810.05 thus Ho is accepted; score of attitude combined with learning  achievement between the two groups of  students is 0.4900.05 and  0.6810.05, thus Ho is accepted; the degree of differences attitudes and learning achievements  between the two group of students is  99.12597.875, meaning the average of the students from complete families is better than the students’  single-parent families.Penelitian ini menggunakan rancangan penelitian kuantitatif. Pengambilan sampel menggunakan tehnik sampling purposive. Untuk menguji hasil tes skala sikap dan tes hasil belajar dihitung sekaligus digunakan program anates. Hasil penelitian menunjukkan: sikap antara siswa  yang diasuh oleh keluarga lengkap dan keluarga single parent mencapai besaran 0,4900,05 sehingga Ho diterima; prestasi belajar siswa keluarga lengkap dan siswa keluarga single parent mencapai skor 0,6810,05 sehingga Ho diterima; kombinasi sikap dan prestasi belajar  antara  siswa keluarga lengkap dan siswa keluarga single parent menyatakan 0,4900,05 dan 0,6810,05 sehingga Ho diterima; perbedaan sikap dan prestasi belajar antara siswa yang diasuh oleh keluarga lengkap bila dibandingkan dengan siswa yang diasuh oleh keluarga single parent mencapai besaran 99,12597,875 yang berarti rerata siswa yang berasal dari keluarga utuh memiliki rerata lebih baik dari para siswa yang berasal dari keluarga single parent.Kata kunci: sikap, prestasi belajar, keluarga utuh, keluarga single parent.